Narečna podoba mariborskega predmestja - Zorko, Zinka (Jezik in slovstvo, 1989)
The dialects of Maribor represent a contact between the various dialects of the Štajerska region: the Panonian, the "Slovenske gorice" and the "Kozjak" variant, the North-Styrian and the dialects of the Eastern and Northern part of the Pohorje.
Keywords: Slovene dialects; slovenska narečja; dialectology; dialektologija; Maribor